Valeton Phytoconstituents from Curcuma Phaeocaulis as Prion Protein Mutant V210I Inhibitors: A Computational Docking and Virtual Screening Study - Richa Sanyal; Samiksha Bhor (International Journal of Biochemistry and Biomolecule Research, 2023)
Objective: Creutzfeldt-Jakob disease (CJD), a neurological disorder that is sporadic, fatal, communicable, and worsens rapidly, is caused by abnormal folding of prion proteins. Identifying and assessing the potential of phytocompounds from the Curcuma phaeocaulis Valeton plant as a new therapeutic candidate aimed at the treatment of CJD is the objective of this research article. Methods: In this experiment, we assessed outcomes following an in-silico assessment to design a new oral treatment for Creutzfeldt-Jakob disease. (CJD). Phytocompounds from Curcuma phaeocaulis Valeton believed to have therapeutic effects were selected, put through a comprehensive virtual screening in this study, and screened for pharmacology and toxicology. Eventually, the screening was completed by docking the selected compounds with PyRx and Biovia against the prion protein target. Results: Germacrone, Cyclocurcumin, and demethoxycurcumin were found to be potentially effective therapeutic drugs against the target prion protein in docking analysis. Conclusion: According to this analysis, Curcuma phaeocaulis valeton can be a beneficial therapeutic herb for further research on the treatment of Creutzfeldt-Jakob disease.
Keywords: ADMET; Curcuma phaeocaulis valeton; creutzfeldt-jakob disease (CJD); molecular docking; prion disease; toxicity prediction